Hydrodynamic modelling of flexible tidal turbine blades - Zilic De Arcos, F; Vogel, C; Willden, R (Technical Committee of the European Wave and Tidal Energy Conference, 2019)
The current work is an analysis of the hydrodynamic effects of the different deformation mechanisms that affect axial-flow tidal turbines with the intention of understanding to what extent hydroelastic effects could be employed to improve the performance or to reduce the loads in rotors. For that, a simple hydroelastic model is employed to obtain the deformed geometries of a turbine, which are then de-coupled into edgewise, flapwise, and twist deformations. The deformation data is used to analyse, by the means of blade-resolved CFD simulations, four different cases, for which the rotor geometries were rebuilt: The originally designed rotor simulated as if it was a rigid structure; the blade with just flapwise deformation, retaining the original twist angles; only the twist deformation and; finally, the deformed rotor with all the deformation components, as obtained from the hydroelastic model. For each case, three different tip-speed ratios were analysed (4.0, 5.5 and 7.0) at a flow speed of 4.5 [m/s]. It is from these simulations that the influence of the different deformation mechanisms is quantified, as well as the relative independence and interaction of the hydrodynamic phenomena associated with them.